Nanocellulose-based flexible thermoelectric material and preparation method thereof
By forming latex particle templates in conductive polymer monomers and polymerizing conductive polymer chain segments on the surface of nanocellulose, the problem of degradation of conductivity is solved, and the preparation of nanocellulose-based flexible thermoelectric materials with high conductivity is realized. Application in the field of thermoelectricity.
Patent Information
- Application Number
- CN202411648843.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-19
AI Technical Summary
Existing cellulose conductive materials have challenges in the uniform bonding and conductivity maintenance of conductive polymer chains, resulting in a decrease in conductivity and making it difficult to meet the application needs in the thermoelectric field.
By adding oxidant to the conductive polymer monomer to form latex particles, and polymerizing conductive polymer chain segments on the surface of nanocellulose using latex particles as templates to form fibrous conductive polymers, achieving uniform binding between conductive polymers and nanocellulose .
It realizes uniform polymerization of conductive polymers in the overall structure of nanocellulose, maintains high conductivity, solves the problem of decreased conductivity, and is suitable for applications in the field of thermoelectricity.
Smart Images

Figure CN119505188A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermoelectric materials, and in particular to a nano-cellulose-based flexible thermoelectric material and a preparation method thereof. Background Art
[0002] As the core technology for developing distributed clean energy or microgrids, solid-state power generation technology can be divided into three types: piezoelectric, friction and thermoelectric. Thermoelectric has been widely used in temperature difference power generation in military aerospace equipment, medical equipment, etc., and is the solid-state power generation technology with the most development potential. The base materials of traditional thermoelectric devices are aluminum oxide and copper sheets. The overall brittleness of the materials is high. In actual application, it is easy for micro devices to be incompatible and their performance to drop significantly due to environmental problems. Therefore, the development of device materials that meet flexibility and micro-processing is conducive to solving challenges such as the decline in thermoelectric efficiency faced by device miniaturization.
[0003] Organic semiconductors are new materials with both high electrical conductivity and low thermal conductivity. Common types include acetylene, aniline, thiophene, etc. Among them, poly (3,4-ethylenedioxythiophene), an organic polymer belonging to the thiophene family, is a conductive material that has been studied more. It has the characteristics of adjustable molecular structure and energy gap and high electrical conductivity. However, the defects of high-purity poly (3,4-ethylenedioxythiophene) such as poor water solubility, low mechanical strength, and inability to form a self-supporting film have seriously restricted its performance, application and development. Traditional countermeasures such as the use of surfactant coating (poly (3,4-ethylenedioxythiophene: poly (styrene sulfonate)) will reduce the overall conductivity of the material due to the wrapping of the conductive main material by the low-conductive surfactant component. Therefore, people often hope to polymerize poly (3,4-ethylenedioxythiophene) in situ on the surface of organic materials to maintain the overall conductivity, flexibility and film processability of the material for use in micro devices.
[0004] Nanocellulose is extracted from natural cellulose sources (wood, bamboo, etc.) and has the characteristics of high aspect ratio, high strength, low thermal conductivity and easy modification. This effectively meets the high strength, low thermal conductivity and lightweight flexibility requirements of thermoelectric device plates. Therefore, it is also widely used in solar cells, micro sensors and wearable devices. For example, Chinese patent CN117903471A prepares a bacterial cellulose flexible conductive gel film material with a dense conductive layer and a loose inner layer by in-situ polymerization of conductive polymer monomers and doping with negatively ionized nanocrystals. The product has a conductivity of 10 -4 ~10 -1 S cm -1Order of magnitude; Chinese patent CN117558977A prepares highly conductive nanocellulose by introducing sulfosalicylic acid as the interface adhesive between 3,4-ethylenedioxythiophene and nanocellulose. In addition, there are also literature reports that polydopamine is added as an adhesive to prepare poly (3,4-ethylenedioxythiophene)-polydopamine-nanocellulose conductive nanofibers with a core-sheath structure.
[0005] However, the cellulose conductive materials reported so far have certain problems:
[0006] (1) Since cellulose itself is not conductive and its chemically reactive sites are relatively dispersed, the current method of polymerizing conductive polymers on cellulose using in situ polymerization often makes it difficult for the conductive polymer chains to combine in the overall internal structure of cellulose (film, block, etc.) to form a uniform and coherent conductive path.
[0007] (2) Although adding viscous substances such as polymers can improve the compatibility between material components, most additives do not have good electrical conductivity. Therefore, the conductivity of the conductive material prepared by this method will decrease due to the decrease in the proportion of the conductive component, which is not conducive to its application in the thermoelectric field.
[0008] Therefore, building a strong conductive network with cellulose as the skeleton is crucial for the preparation of flexible cellulose-based materials with high thermoelectric efficiency, and is also one of the key issues in further applying cellulose special materials in the field of thermoelectricity. Summary of the invention
[0009] The object of the present invention is to provide a nanocellulose-based flexible thermoelectric material and a preparation method thereof, so as to achieve uniform polymerization of conductive polymer materials in the overall structure of nanocellulose without the need for additional adhesives, thereby obtaining a nanocellulose-based flexible thermoelectric material with high conductivity.
[0010] To achieve the above objectives, the present technical solution provides a method for preparing a nanocellulose-based flexible thermoelectric material, comprising the following steps:
[0011] An oxidant and a conductive polymer monomer are added into an anionic surfactant solution to react and obtain a fibrous conductive polymer, wherein the oxidant contains iron or amine radicals;
[0012] Nanocellulose solution, oxidant and conductive polymer monomer are sequentially added to the fibrous conductive polymer and reacted to obtain the nanocellulose-based flexible thermoelectric material.
[0013] This scheme forms latex particles by gradually adding oxidants to conductive polymer monomers, and polymerizes fibrous conductive polymers through conductive polymer monomers using the latex particles as templates. A large number of long-chain fibrous conductive polymers are polymerized on the surface of nanocellulose under the action of electric charges to form long-chain conductive polymer segments. These long-chain conductive polymers can not only evenly cover the surface of nanocellulose, but also act as bridges to promote electron transfer between nanocelluloses, so that the final nanocellulose-based flexible thermoelectric material has high conductivity.
[0014] Furthermore, the anionic surfactant of the present invention is selected from one or any combination of a sulfate anionic surfactant, a sulfonic acid anionic surfactant or a fatty acid salt anionic surfactant. Preferably, the anionic surfactant is a sulfonic acid anionic surfactant, and the sulfonic acid group (-OSO3 - ). Since sulfonate groups generally exist as counter ions of conductive polymers, that is, when there are sulfonate groups on the surface of nanocellulose, the fibrous conductive polymer can better exert its conductive effect.
[0015] Furthermore, when the anionic surfactant is a fatty acid salt anionic surfactant, the anionic surfactant is one or a combination of two or more of fatty acid methyl ester sodium sulfonate, fatty acid sulfoalkyl ester, fatty acid sulfoalkyl amide, and sodium succinate sulfonate.
[0016] Furthermore, when the anionic surfactant is a sulfate-based anionic surfactant, the anionic surfactant is one or a combination of two or more of sulfated castor oil, sodium dodecyl sulfate, sodium hexadecyl sulfate, sodium octadecyl sulfate, and sulfonated lignin.
[0017] Furthermore, when the anionic surfactant is a sulfonic acid anionic surfactant, the anionic surfactant is one or a combination of two or more of dioctyl sodium sulfosuccinate, sodium dodecylbenzene sulfonate, sodium hexadecylbenzene sulfonate, and sodium octadecylbenzene sulfonate.
[0018] Preferably, the anionic surfactant is selected from sodium dodecyl sulfate, or the anionic surfactant is selected from sodium dodecyl sulfate and sodium fatty acid methyl ester sulfonate, fatty acid sulfonalkyl ester, fatty acid sulfonalkyl amide, sodium succinate sulfonate, sulfated castor oil, sodium hexadecyl sulfate, sodium octadecyl sulfate, sulfonated lignin, dioctyl sodium sulfosuccinate, sodium dodecylbenzene sulfonate, sodium hexadecylbenzene sulfonate, sodium octadecylbenzene sulfonate, a combination of one or more of the above.
[0019] Further, the concentration of the anionic surfactant is (5-100) mmol anionic surfactant / 100 mL water. Preferably, the concentration of the anionic surfactant is (5-30) mmol / 100 mL water.
[0020] Further, the purpose of the oxidant containing iron or amine radical is to initiate polymerization reaction and oxidize the conductive polymer monomer to help the formation of conductive polymer conjugated chains and charge carriers (such as holes). When the oxidant contains iron, the oxidant is selected from one or more combinations of ferric chloride, ferric p-toluenesulfonate, ferric hydroxide, and ferric nitrate. When the oxidant contains amine radical, the oxidant is selected from ammonium persulfate.
[0021] Preferably, the oxidant is selected from ferric chloride, or a combination of ferric chloride and one or more of ferric p-toluenesulfonate, ammonium persulfate, ferric hydroxide, and ferric nitrate.
[0022] Furthermore, the molar ratio of the oxidant, the conductive polymer monomer and the anionic surfactant is (1-50:1-50:1-100). This has the advantage of maintaining the stable formation of the oxidant-containing micelle particles to polymerize the long-chain conductive polymer fibers.
[0023] Preferably, the molar ratio of the conductive polymer monomer to the oxidant is 8:16.
[0024] Furthermore, the conductive polymer monomer includes one or a combination of two or more of poly (3,4-ethylenedioxythiophene), polyaniline, polypyrrole and polythiophene.
[0025] Preferably, the conductive polymer monomer is selected from 3,4-ethylenedioxythiophene monomer, or a combination of 3,4-ethylenedioxythiophene monomer and one or more of polyaniline, polypyrrole and polythiophene.
[0026] Furthermore, an oxidant and a conductive polymer monomer are added to an anionic surfactant solution to react to obtain a fibrous conductive polymer, wherein the reaction conditions are a reaction temperature of 45 to 100° C. and a reaction time of 1 to 24 hours.
[0027] It should be noted that in this scheme, an oxidant is added dropwise to an anionic surfactant solution and a conductive polymer monomer is added, latex particles are formed between the oxidant and the anionic surfactant, and the conductive polymer monomer uses the latex particles as a template to grow rod-shaped fibrous conductive polymers. When the oxidant is ferric chloride and the anionic surfactant is sodium dodecyl sulfate, ferric chloride is added dropwise to the sodium dodecyl sulfate to form ferric chloride latex particles, and the conductive polymer monomer uses the ferric chloride latex particles as a template to polymerize into fibrous conductive polymers.
[0028] Furthermore, nanocellulose solution, oxidant and conductive polymer monomer are added to the fibrous conductive polymer in sequence, reacted at a set reaction temperature for a period of time and then centrifuged, the lower layer of the precipitate is taken and repeatedly dissolved and centrifuged with ethanol aqueous solution to obtain the nanocellulose-based flexible thermoelectric material.
[0029] Furthermore, the nanocellulose solution is a nanocellulose solution containing -OSO3 - Functional groups on sulfurized nanocellulose.
[0030] Furthermore, the mass concentration of the nanocellulose solution is 0.1-1.0 wt %. This has the advantage of controlling the viscosity of the nanocellulose solution to prevent affecting the progress of the polymerization reaction system.
[0031] Furthermore, in the step of sequentially adding the nanocellulose solution, the conductive polymer monomer and the oxidant to the fibrous conductive polymer, the selection of the conductive polymer monomer and the oxidant is the same as that of the conductive polymer monomer and the oxidant when the fibrous conductive polymer is formed.
[0032] Furthermore, the molar ratio of the conductive polymer monomer and the oxidant added to the fibrous conductive polymer in sequence is 8:16.
[0033] Furthermore, the nanocellulose solution, the oxidant and the conductive polymer monomer are sequentially added to the fibrous conductive polymer and reacted under the following reaction conditions: the reaction temperature is 45 to 100° C. and the reaction time is 1 to 24 hours.
[0034] Furthermore, after reacting for a period of time at a set reaction temperature, the centrifugal condition is 6000-10000 r / min, the centrifugal time is 4-10 min, and the upper layer of the solution obtained after centrifugation is a clear orange-yellow solution, and the lower layer is a black precipitate.
[0035] Furthermore, the volume ratio of ethanol to water in the ethanol aqueous solution is 50:(0-100), preferably, the volume ratio of ethanol to water in the ethanol aqueous solution is 50:50.
[0036] Furthermore, the centrifugal conditions for repeated dissolution and centrifugation of the ethanol aqueous solution are 6000-10000 r / min, the centrifugal time is 4-10 min, and the solution after centrifugation is a clear colorless to light green solution on the upper layer and a black precipitate on the lower layer.
[0037] Furthermore, the yield of the nanocellulose-based flexible thermoelectric material is 50-85%.
[0038] It should be noted that the second addition of nanocellulose, oxidant and conductive polymer monomer in this scheme uses the nanocellulose in the solution as a new polymerization template. The fibrous conductive polymer is polymerized on the surface of the nanocellulose under the charge interaction force to form long-chain segments of conductive polymer. These long-chain conductive polymers can not only evenly cover the surface of the nanocellulose, but also act as bridges to promote electron transfer between different nanocellulose roots to maintain the overall high conductivity of the material. Finally, the residual anionic surfactant in the material can be removed by centrifugation to further improve the overall conductivity of the material.
[0039] The present invention further provides a nanocellulose-based flexible thermoelectric material, which is obtained according to the preparation method of the above-mentioned nanocellulose-based flexible thermoelectric material, and includes nanocellulose as a substrate, and conductive polymer long chain segments composed of fibrous conductive polymers polymerized on the surface of the nanocellulose.
[0040] Furthermore, the nanocellulose-based flexible thermoelectric materials provided by this solution are applied in the field of thermoelectricity, such as real-time monitoring equipment in extreme environments, wearable electrode treatment patches, heat recovery devices and other scenarios.
[0041] Compared with the prior art, this technical solution has the following characteristics and beneficial effects:
[0042] This solution provides a method for preparing a nanocellulose-based flexible thermoelectric material. Different from the simple use of in-situ polymerization to prepare a conductive polymer-nanocellulose film or the simple mixing of nanocellulose with a conductive polymer, this solution uses the addition of anionic surfactants and oxidants to form a latex particle template, so that the conductive polymer monomer is polymerized with the latex particle template to obtain a rod-shaped fibrous conductive polymer, and then the conductive polymer monomer is polymerized on the surface of the nanocellulose using nanocellulose as a new polymerization template. The conductive performance distribution of the nanocellulose-based flexible thermoelectric material finally obtained by the present invention is more uniform, and the structure is more stable. The electronic transmission and structural morphology of the material can be effectively regulated by controlling the length of the conductive polymer chain segment and the degree of sulfonation on the nanocellulose. It has broad prospects in the application of thermoelectric materials, such as real-time monitoring equipment in extreme environments, wearable electrode treatment patches, heat recovery devices, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 FIG. 4 is a scanning electron microscope (SEM) image of fibrous poly (3,4-ethylenedioxythiophene) according to an embodiment of the present invention.
[0044] Figure 2 This is the infrared spectrum (FT-IR) spectrum of poly (3,4-ethylenedioxythiophene)-nanocellulose material.
[0045] Figure 3This is the laser Raman spectrum (Raman) of poly (3,4-ethylenedioxythiophene)-nanocellulose material.
[0046] Figure 4 This is the X-ray diffraction (XRD) pattern of poly (3,4-ethylenedioxythiophene)-nanocellulose material.
[0047] Figure 5 This is the structural formula and preparation principle diagram of poly (3,4-ethylenedioxythiophene)-nanocellulose material.
[0048] Figure 6 This is the Zeta potential diagram of poly (3,4-ethylenedioxythiophene)-nanocellulose material.
[0049] Figure 7 This is the SEM image of poly (3,4-ethylenedioxythiophene)-nanocellulose material.
[0050] Figure 8 This is an atomic force microscope (AFM) image of poly (3,4-ethylenedioxythiophene)-nanocellulose material.
[0051] Fig. 9 (a) Electrical conductivity of poly (3,4-ethylenedioxythiophene)-nanocellulose material; (b) Seebeck coefficient; (c) thermoelectric power factor; (d) electron transition barrier diagram. DETAILED DESCRIPTION
[0052] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0053] It is to be understood that the term "one" should be understood as "at least one" or "one or more", that is, in one embodiment, the number of an element may be one, while in another embodiment, the number of the element may be multiple, and the term "one" should not be understood as a limitation on the quantity.
[0054] Embodiment 1
[0055] Preparation of poly (3,4-ethylenedioxythiophene)-nanocellulose-based materials
[0056] The structural formula of poly (3,4-ethylenedioxythiophene)-nanocellulose and the preparation principle diagram of poly (3,4-ethylenedioxythiophene)-nanocellulose are shown in the attached figure. Figure 5 shown.
[0057] (1) Preparation of nanocellulose: 40 g of wood strips were soaked in a 4% peracetic acid solution at pH 4.5, and reacted at 85°C for 7 h to obtain cellulose with delignin. The delignined cellulose was soaked in an aminosulfonic acid / N,N-dimethylformamide solution, wherein the molar ratio of aminosulfonic acid to cellulose (OH) functional group was 1:1. After mixing, the mixture was subjected to a sulfation reaction at 85°C in a water bath for 2 h to obtain sulfonated cellulose, which was then pulped using a blender to obtain nanocellulose.
[0058] (2) Preparation of poly (3,4-ethylenedioxythiophene)-nanocellulose: 30 mmol of sodium dodecyl sulfate was dissolved in 100 mL of water, 10 mL of 8 mmol of ferric chloride solution was added dropwise to the sodium dodecyl sulfate solution and stirred at 50°C for 10 min, 4 mmol of 3,4-ethylenedioxythiophene was added dropwise to the mixed solution and stirred at 50°C for 3 h. After 3 h, 27.4 g of 0.25 wt% nanocellulose solution, 10 mL of 8 mmol of ferric chloride solution and 4 mmol of 3,4-ethylenedioxythiophene were added dropwise to the mixed solution in sequence, and stirred at 50°C for 3 h. At the end of the reaction, the solution was dark green or blue-black. The liquid after the reaction was transferred to a centrifuge tube, centrifuged at 9000 r / min for 5 min, and the liquid was immediately poured out to obtain a black solid remaining on the tube wall. Then add 50% ethanol aqueous solution to the centrifuge tube and mix evenly. After centrifugation at 9000 r / min for 5 minutes, pour out the liquid immediately to obtain a black solid remaining on the tube wall. After repeating the above operation three times, the poly (3,4-ethylenedioxythiophene)-nanocellulose product can be obtained.
[0059] Structural characterization of poly (3,4-ethylenedioxythiophene)-nanocellulose-based materials:
[0060] The solution was sampled after 3 hours in the preparation process of poly (3,4-ethylenedioxythiophene)-nanocellulose and observed by scanning electron microscope (SEM). Figure 1 As shown, it can be seen that after 3 hours of reaction, the conductive polymer in the solution presents a fibrous morphology with a length of >5 μm, thereby verifying the production of fibrous conductive PEDOT polymers.
[0061] The infrared spectrum scanning results of the prepared poly 3,4-ethylenedioxythiophene-nanocellulose material are as follows: Figure 2 As shown in the figure, it can be seen that the prepared poly 3,4-ethylenedioxythiophene-nanocellulose spectrum has a peak at 1236 cm -1 There is a stretching vibration peak of O=S=O at 826cm -1 The presence of a bending vibration peak of COS at 1484 cm-1 verifies the presence of nanocellulose components in poly(3,4-ethylenedioxythiophene)-nanocellulose. -1There is a stretching vibration peak of C=C; at 1325cm -1 There are bending vibration peaks of CC at 1182, 1134, 1090, 1054 cm -1 There is a bending vibration peak of COC at 970cm -1 and 929cm -1 The presence of a bending vibration peak of CSC at the position verifies that fibrous 3,4-ethylenedioxythiophene polymerization was successfully performed on the surface of nanocellulose to synthesize poly (3,4-ethylenedioxythiophene)-nanocellulose.
[0062] The Raman spectrum of the prepared poly (3,4-ethylenedioxythiophene)-nanocellulose material was scanned, and the results were as follows: Figure 3 As shown, visible, at 438cm -1 、572cm -1 and 989cm -1 The three bands centered at 1101 cm reflect the deformation of the ethylene oxide ring in the structure of poly(3,4-ethylenedioxythiophene); -1 There is a Raman peak related to the deformation of the COC bond at 1262cm -1 C α -C α 'The Raman peak related to the inter-ring stretching; at 1368cm -1 、1429cm -1 and 1509cm -1 The Raman peaks at β -C β 'Stretch, C α -C β (-O)Stretch and Asymmetry C α -C β Stretching related.
[0063] The prepared poly (3,4-ethylenedioxythiophene)-nanocellulose material was subjected to X-ray diffraction, and the results were as follows: Figure 4 As shown, it can be seen that 2θ = 18.1° and 2θ = 22.7° are the (1-10 / 110) crystal plane and (200) crystal plane of nanocellulose respectively; the sharp peaks formed by the stacking crystallization between PEDOT chains appear at 2θ = 6.7° (d 100), 2θ = 12.8° (d 200), 2θ = 19.4° (d 300) and 2θ = 25.9°. Among them, the XRD peak at 2θ = 25.9° (lattice spacing ) is attributed to the π–π inter-stacking distance (d 020) of the PEDOT chains.
[0064] The above experimental results all verify the successful synthesis of poly (3,4-ethylenedioxythiophene)-nanocellulose.
[0065] Performance test of poly (3,4-ethylenedioxythiophene)-nanocellulose-based materials:
[0066] The prepared poly (3,4-ethylenedioxythiophene)-nanocellulose was subjected to a Zeta potential test, and the results are as follows: Figure 6 As shown, it can be seen that the zeta of poly (3,4-ethylenedioxythiophene)-nanocellulose is 2.27 mV, indicating that poly (3,4-ethylenedioxythiophene) and nanocellulose are closely combined, the surface charge is low, and the attraction between particles is large.
[0067] The prepared poly (3,4-ethylenedioxythiophene)-nanocellulose was photographed by SEM, and the results are as follows: Figure 7 As shown, it can be seen that the surface of poly (3,4-ethylenedioxythiophene)-nanocellulose is relatively smooth and the fiber size is about 3-5 μm.
[0068] The prepared poly (3,4-ethylenedioxythiophene)-nanocellulose was tested by atomic force microscopy (AFM). Figure 8 As shown, it can be seen that the size of poly (3,4-ethylenedioxythiophene)-nanocellulose fibers is about 3-5 μm, and the diameter of a single fiber is about 40 nm.
[0069] The above data all indicate that poly (3,4-ethylenedioxythiophene)-nanocellulose was successfully prepared, and a uniform poly (3,4-ethylenedioxythiophene) layer was successfully polymerized on the nanocellulose.
[0070] Example 2 Thermoelectric performance of poly (3,4-ethylenedioxythiophene)-nanocellulose
[0071] Weigh 0.0109 g of poly (3,4-ethylenedioxythiophene)-nanocellulose with a net content of 3,4-ethylenedioxythiophene (EDT)-nanocellulose and dissolve it in 300 mL of deionized water. Filter the filter cake on a suction filtration device. Use a vacuum hot press to heat-press the filter cake into a poly (3,4-ethylenedioxythiophene)-nanocellulose film.
[0072] The thermoelectric performance of the prepared poly (3,4-ethylenedioxythiophene)-nanocellulose film was tested using a Seebeck resistance meter. Fig. 9 (a) to Fig. 9 As shown in (c), the conductivity of poly (3,4-ethylenedioxythiophene)-nanocellulose at 30°C is 5033 S·m -1 ; Seebeck coefficient is 19.0μV·K -1 The calculated thermoelectric power factor of poly (3,4-ethylenedioxythiophene)-nanocellulose is 1.81 μW·m -1 K -2 As the temperature rises, the conductivity of the film decreases slightly, the Seebeck coefficient increases significantly, and the maximum thermoelectric power factor can reach 2.45μW·m -1K -2 .
[0073] Further regression analysis was performed on the measured thermoelectric performance values, and the results are as follows: Fig. 9 As shown in (d) in the figure, the energy required for electron transition in poly (3,4-ethylenedioxythiophene)-nanocellulose is 11 meV.
[0074] The above data all show that the prepared poly (3,4-ethylenedioxythiophene)-nanocellulose has good thermoelectric properties.
[0075] Example 3 Effect of different ratios on the reaction
[0076] Referring to Example 1, the ratio of the amount of each addition of 3,4-ethylenedioxythiophene to the amount of each addition of ferric chloride was changed, and other conditions remained unchanged. The reaction and treatment were carried out according to the scheme of Example 1. The specific results are shown in Table 1. It can be seen that when the amount ratio of 3,4-ethylenedioxythiophene to ferric chloride is 8:16, the yield of poly 3,4-ethylenedioxythiophene-nanocellulose is the highest, which can reach 75.4%, so this ratio is preferably used for preparation.
[0077] Table 1 Effect of different ratios of 3,4-EDT and ferric chloride on the yield of poly (3,4-EDT)-nanocellulose
[0078]
[0079]
[0080] Example 4 Effect of different concentrations of ethanol-water ratio on the product
[0081] Referring to Example 1, the ethanol-water ratio of the centrifuged solution was changed, and other conditions remained unchanged, and the reaction and treatment were carried out according to the scheme of Example 1. The specific results are shown in Table 2: It can be seen that when the ethanol-water volume ratio is 50:50, the yield of poly (3,4-ethylenedioxythiophene)-nanocellulose is the highest, and the yield can reach 75.4%, so this solvent is preferably used for preparation.
[0082] Table 2 Effect of different ratios of ethanol aqueous solution on the yield of poly (3,4-ethylenedioxythiophene)-nanocellulose
[0083]
[0084] Comparative Example 1 Performance of commercially available poly 3,4-ethylenedioxythiophene thermoelectric material
[0085] The corresponding performance results of several commonly reported commercially available or cellulose-based poly (3,4-ethylenedioxythiophene) thermoelectric materials are shown in Table 3.
[0086] Table 3 Comparison of thermoelectric properties of poly (3,4-ethylenedioxythiophene)-nanocellulose and other materials
[0087]
[0088]
[0089] From the performance comparison of other materials in Table 3, the poly (3,4-ethylenedioxythiophene)-nanocellulose of the present invention has excellent thermoelectric performance.
[0090] Comparative Example 2 Effect of not adding anionic surfactant
[0091] Preparation of amorphous poly (3,4-ethylenedioxythiophene)-nanocellulose: First, add 20 mL of 16 mmol of ferric chloride solution to 27.4 g of 0.25 wt% nanocellulose solution, and stir at 50°C for 30 min to disperse evenly. Add 8 mmol of 3,4-ethylenedioxythiophene dropwise to the mixed solution, and stir at 50°C for 3 h. Other operations are the same as in Example 1, and the final product prepared is amorphous poly (3,4-ethylenedioxythiophene)-nanocellulose.
[0092] Referring to Example 2, the thermoelectric performance of amorphous poly (3,4-ethylenedioxythiophene)-nanocellulose was tested and compared with the poly (3,4-ethylenedioxythiophene)-nanocellulose prepared by the present invention. The corresponding performance results are shown in Table 4.
[0093] Table 4 Comparison of thermoelectric properties of poly (3,4-ethylenedioxythiophene) nanocellulose and amorphous poly (3,4-ethylenedioxythiophene) nanocellulose at different temperatures
[0094]
[0095] Comparing the thermoelectric properties of amorphous poly (3,4-ethylenedioxythiophene)-nanocellulose prepared without adding anionic surfactant and poly (3,4-ethylenedioxythiophene)-nanocellulose at different temperatures in Table 4, the electrical conductivity of the poly (3,4-ethylenedioxythiophene)-nanocellulose of the present invention is significantly higher than that of the amorphous poly (3,4-ethylenedioxythiophene)-nanocellulose synthesized by simple in-situ polymerization reaction without adding anionic surfactant, which indicates that poly (3,4-ethylenedioxythiophene)-nanocellulose has more superior thermoelectric properties.
[0096] The present invention is not limited to the above-mentioned optimal implementation mode. Anyone can derive other various forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, all technical solutions that are the same or similar to those of the present application fall within the protection scope of the present invention.
Claims
1. A method for preparing a nanocellulose-based flexible thermoelectric material, characterized in that: The following steps are involved: An oxidant and a conductive polymer monomer are added to an anionic surfactant solution to react to obtain a fibrous conductive polymer, wherein the oxidant contains iron or amine radicals; a nanocellulose solution, an oxidant and a conductive polymer monomer are sequentially added to the fibrous conductive polymer and reacted to obtain a nanocellulose flexible thermoelectric material.
2. The method for preparing a nanocellulose-based flexible thermoelectric material according to claim 1, characterized in that: The anionic surfactant is selected from one or any combination of a sulfate anionic surfactant, a sulfonic acid anionic surfactant or a fatty acid salt anionic surfactant.
3. The method for preparing the nanocellulose-based flexible thermoelectric material according to claim 1, characterized in that: When the oxidant contains iron, the oxidant is selected from one or a combination of two or more of ferric chloride, ferric p-toluenesulfonate, ferric hydroxide, and ferric nitrate; when the oxidant contains an amine radical, the oxidant is selected from ammonium persulfate.
4. The method for preparing a nanocellulose-based flexible thermoelectric material according to claim 1, characterized in that: The concentration of the anionic surfactant is (5-100) mmol anionic surfactant / 100 mL water.
5. The method for preparing the nanocellulose-based flexible thermoelectric material according to claim 1, characterized in that: The conductive polymer monomer includes one or a combination of two or more of poly (3,4-ethylenedioxythiophene), polyaniline, polypyrrole and polythiophene.
6. The method for preparing a nanocellulose-based flexible thermoelectric material according to claim 1, characterized in that: The molar ratio of the oxidant, the conductive polymer monomer and the anionic surfactant is 1-50:1-50:1-100.
7. The method for preparing a nanocellulose-based flexible thermoelectric material according to claim 1, characterized in that: Nanocellulose solution is with -OSO3 - Functional groups on sulfurized nanocellulose.
8. The method for preparing the nanocellulose-based flexible thermoelectric material according to claim 1, characterized in that: The mass concentration of the nanocellulose solution is 0.1-1.0 wt%.
9. A nanocellulose-based flexible thermoelectric material, characterized in that: According to the preparation method of the nanocellulose-based flexible thermoelectric material according to any one of claims 1 to 8, the material comprises nanocellulose as a substrate, and long chains of conductive polymers composed of fibrous conductive polymers polymerized on the surface of the nanocellulose.
10. The nanocellulose-based flexible thermoelectric material according to claim 9, characterized in that: Applied in the field of thermoelectric materials.
Citation Information
Patent Citations
Polymer electrolyte membrane of ion battery
CN117558977A
Biocompatible flexible transparent conductive film, preparation method and application
CN117903471A
Preparing method of conducting polymer / regenerated cellulose fiber composite material
CN106146836A
Preparation method of doped polyaniline / nano microcrystalline cellulose composite material
CN111234525A
Thermoelectric conversion element
JP2021073694A